Խոր ինֆիլտրատիվ էնդոմետրիոզի ախտորոշման և բուժման արդիական խնդիրները - Դրամպյան, Ա. Ա. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Despite the advances in the diagnosis and treatment of endometriosis, the management of patients with deep infiltrative endometriosisis is still challenging. Challenges in the management of patients with deep infiltrative endometriosis depend on classification, clinical symptoms (often with an atypical course), and strong variability in the severity of the disease. Therefore, the management mainly depends on the precise diagnosis, the patient’s age, duration of the pathology, clinical manifestation of the disease, the reproductive wishes, as well as the risks, adverse effects, and the cost-effectiveness of the treatment. A thorough analysis of anamnesis, laboratory tests, and ultrasound examinations can suggest endometriosis in up to 70% of cases, but not to diagnose the spread and localization of endometriosis. In addition, currently 20-30% of cases of deep infiltrative endometriosis don’t have typical manifestations of the pathology, do not even allow to suspect pathology. When it comes to treatment, in addition of removing endometriosis, there is another difficulty: preventing of recurrences and restoring the reproductive function. In this article we present the challenges in diagnosis and treatment of patients with deep infiltrative endometriosis and infertility due to the atypical course of the pathology, the advance stages of the diseas, the localization, and the long duration of the process. The article describes the methods of complete removal of endometrio-sis/implants performed in women of reproductive age, the tactics of reconstructive-plastic interventions, the technical difficulties of these interventions, as well as the avoidance of radical intervention in deep endometriosis. It has been established that the goal of laparoscopic surgery for deep infiltrative endometriosis significantly depends on the nature of the pathology, the extent, depth, involovement of the surrounding organs, and the qualification of the endoscopist. The aim of this study was to evaluate the difficulties of diagnosis and treatment of patients with deep infiltrative endometriosis and infertility in current terms. Несмотря на успехи в диагностике и лечении эндометриоза, диагностика и лечение пациентов с глубоким инфильтративным эндометриозом продолжают оставаться одной из проблем современной гинекологии. Трудности в ведении пациентов с глубоким инфильтративным эндометриозом связаны с классификацией, клинической картиной (часто с атипическим течением), широкой вариабельностью тяжести заболевания. Следовательно, тактика ведения в основ-ном зависит от правильного диагноза, возраста пациентки, типа и стадии заболевания, характера симптомов, репродуктивных целей, а также рисков, побочных эффектов и экономической эффективности лечения. Путем тщательного анализа анамнеза,клинических и лабораторных тестов, сонографии, можно заподозрить наличие эндометриоза в 70 % случаев, но не диагностировать распространенность и локализацию эндометриоза. Кроме того, в настоящее время 20-30% случаев глубокого инфильтративного эндометриоза проходят без типичных проявлений патологии, не позволяя даже заподозрить патологию. Что касается лечения, помимо устранения очагов эндометриоза возникает необходимость избавления от рецидивов и восстановления репродуктивной функции. В статье представлены проблемы диагностики и лечения пациенток с глубоким инфильтративным эндометриозом и бесплодием в связи с атипичным течением патологии, распространенностью процесса, локализацией и длительностью заболевания. В статье описана тактика полного удаления эндометриоидных очагов/имплантов у женщин репродуктивного возраста,тактика реконструктивно- пластических вмешательств и технические сложности этих вмешательств. Также приводится обоснование необходимости воздержания от радикальных вмешательств в случае глубоких инфильтративных очагов в соседних органах.
Keywords: Գինեկոլոգիա